Variables Influencing Nurses' Adherence to Personal Protective Equipment (PPE) Utilization at PKU Muhammadiyah Hospital Bantul - Ningsih, Atni Setiyo; Suryani, Dyah; Hariyono, Widodo (Epidemiology and Society Health Review (ESHR), 2024)
Background: A hospital is a health service facility that provides outpatient and inpatient patient services. Hospitals can also be a source of infection for officers, patients, and other visitors. To prevent nosocomial infections in officers, hospitals must protect all health workers, for example, by wearing gloves, masks, gowns, face shields, shoes, and aprons. Compliance with PPE on health workers is supported by a positive attitude from officers and supervision carried out by management. This study aims to determine factors related to compliance with use among nurses. Method: This was quantitative research using correlation with the cross-sectional approach. The population in this study was 130 permanent nurses. The sample was calculated using the Slovin formula, resulting in 100 samples. The respondent was selected via proportional random sampling among the care units. Chi–Square was used to analyze the data. Results: There was a relationship between PPE compliance and age (p=0.005), attitude (p=0.000), and supervision (p=0.016). Meanwhile, factors that were not related to PPE compliance were gender (p=1.000), education (p=0.054), knowledge (p=0.170), facilities (p=0.505), and training (p=0.811). Conclusion: There was a significant relationship between age, attitude supervision, and compliance with PPE in nurses when performing their duties.